2016
DOI: 10.1111/acer.13022
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, Methamphetamine, and Marijuana Exposure Have Distinct Effects on the Human Placenta

Abstract: This is the first human study to show that alcohol, methamphetamine, and marijuana were associated with distinct patterns of pathology, suggesting different mechanisms mediating their effects on placental development. Given the growing body of evidence linking placental abnormalities to neurodevelopmental deficits, these findings may be important in the long-term teratogenic effects of prenatal alcohol and drug exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 51 publications
7
69
0
Order By: Relevance
“…In order to eliminate the effects of other potential confounding factors, we selected only three marijuana smokers without tobacco or alcohol addiction. Previously, studies focused on placental pathological characteristics reported that marijuana exposure was associated with larger placenta [30] and no significant differences in the placental villi between controls and marijuana using mothers [31], while potential effects of marijuana exposure on placental development were still largely unknown. Their findings were not consistent with our present results.…”
Section: Discussionmentioning
confidence: 99%
“…In order to eliminate the effects of other potential confounding factors, we selected only three marijuana smokers without tobacco or alcohol addiction. Previously, studies focused on placental pathological characteristics reported that marijuana exposure was associated with larger placenta [30] and no significant differences in the placental villi between controls and marijuana using mothers [31], while potential effects of marijuana exposure on placental development were still largely unknown. Their findings were not consistent with our present results.…”
Section: Discussionmentioning
confidence: 99%
“…In a new, recently recruited Cape Town cohort, we found that maternal alcohol consumption is associated by guest on May 9, 2018 http://pediatrics.aappublications.org/ Downloaded from with reductions in placental weight. 29 Given the critical role of the placenta in fetal growth, alcoholrelated reductions in placental size may mediate the effects of alcohol exposure on growth in utero. By contrast, the postnatal growth restriction seen in children with the heaviest exposure may reflect different mechanisms, such as alterations in fetal programming, endocrinologic development, postnatal metabolism, and/or feeding behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, smoking pregnant women were protected against eclampsia (Conde‐Agudelo and Belizán, ). A study focused on placental pathological changes in smoking pregnant women, revealed that cigarette use was not associated with chorioamnionitis, villitis, or deciduitis (Carter et al, ). On the contrary, another study evidenced that maternal smoking during pregnancy was associated with lower placental and birth weight, and with a higher placenta‐to‐birth weight ratio, when compared with non‐smoking mothers (Wang et al, ).…”
Section: Maternal Factorsmentioning
confidence: 99%